2001
DOI: 10.1097/00007890-200111150-00012
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Recognition and Impairment of Pig Islet Cells by Baboon Immune Cells

Abstract: This study provides the first data on in vitro comparison of baboon and human cell-mediated recognition and impairment of PICs. Proliferation of PBMCs against PICs involves mainly CD4 T cells, with indirect recognition mediated by baboon or human MHC class II+ APCs. The Th2/Th1 profile of cytokines secreted in response to PICs was similar in baboon and human PBMCs. The model based on alteration of insulin secretion indicates that PIC impairment by whole mononuclear cells was strong and rapid and that a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is noteworthy that even in the presence of this immune reaction, porcine islets were able to remain functional and maintain normoglycemia. This immune response must have been caused by some type of indirect recognition mechanism (42). Questions could be raised about possible complement mediated damage, as Roos et al demonstrated that both anti‐pig IgG and IgM could activate complement with subsequent cytotoxicity (43).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that even in the presence of this immune reaction, porcine islets were able to remain functional and maintain normoglycemia. This immune response must have been caused by some type of indirect recognition mechanism (42). Questions could be raised about possible complement mediated damage, as Roos et al demonstrated that both anti‐pig IgG and IgM could activate complement with subsequent cytotoxicity (43).…”
Section: Discussionmentioning
confidence: 99%
“…Hanganutziu-Deicher (HD) antigens and other sialic acid an-The maximum number of islets reported to be success-tigens have been shown to account for significant anti-suggesting more Th2 than Th1 activity (70). The importance of CD4 + T cells was also demonstrated by Fried-genicity of adult pig islets in vitro (61).…”
Section: Immunological Response To Transplanted Isletsmentioning
confidence: 99%
“…Whilst it is broadly accepted that the most significant cause of porcine islet rejection in the primate is the cell-mediated response [117][118][119], porcine islets are nonetheless susceptible to damage and destruction mediated by anti-pig antibodies and complement [120][121][122].…”
Section: Porcine Islets and Humoral Rejection Following Transplantatimentioning
confidence: 99%